Lietuvių ir latvių bendradarbiavimas priešinantis tautinei priespaudai XIX a. pabaigoje - XX a. pradžioje - Pivoras, Saulius (Lietuvos istorijos studijos, 1998)
This article outlines Lithuanian-Latvian contacts and common measures against the policy of national oppression enacted by the Russian tsar government. It is argued that a Latvian complex of senior brother was an obstacle for broadening of cooperation. More productive cooperation was achieved between Lithuanian and Lattgalian illegal book-spreaders. Lithuanian émigré organizations in Latvia were supported by Latvian organizations and common people. The idea of Lithuanian-Latvian unity was more popular than the idea of unity between the Russian Lithuanians and the Prussian Lithuanians during the 1905 revolution in Lithuania. Lithuanian-Latvian cooperation wasn’t much more qualitatively developed after that.